Legal Analysis of the Position of Female Heirs in the Balinese Customary Inheritance System - I Gusti Putu Ardya Maharani; I Nyoman Bagiastra (Westscience Press, 2025)
This study aims to analyze the legal status of female heirs in the Balinese customary inheritance system, which is traditionally based on the patrilineal principle or kapurusa system, where lineage and inheritance rights are passed down through the male line. In this system, married women are considered part of the husband's family (pradana) and generally do not receive inheritance rights from their family of origin. However, social developments, increasing legal awareness, and the influence of national law have driven a paradigm shift in the position of women in customary inheritance. This study uses a normative legal approach supported by qualitative empirical data through literature studies, legal document analysis, and interviews with Balinese customary leaders and women. The results show that there is a duality of norms between Balinese customary law and national law that guarantees gender equality as stipulated in the 1945 Constitution and the CEDAW Convention. Although customary law still maintains the concept of purusa-pradana, practice in the field has begun to show a shift towards a more inclusive system through the recognition of partial inheritance rights for women. Legally, this change strengthens the principles of non-discrimination and substantive justice, while socially it shows the transformation of cultural values towards equality without eliminating Balinese traditional identity.